Adolescents’ Self and Bullying Victimisation: The Key Role of Gender - Matteo Perazzini; Danilo Bontempo; Marco Giancola; Simonetta D’Amico; Enrico Perilli (Children)
Background/Objectives: The primary factors influencing victimisation in bullying have recently become a topic of debate in the psychological literature. This research sought to explore the association between self-criticism (as captured in terms of inadequate self, hated self, and reassured self) and bullying victimisation, also addressing the moderating effects of gender. Methods: This study relies on a cross-sectional research design, enrolling a sample of 328 adolescents (Mage = 14.93; SDage = 0.81; 162 females, 49.4%). Participants completed a short questionnaire about their age, gender, and family’s socio-economic status. They also answered questions from the Forms of Self-Criticising/Attacking and Self-Reassuring Scale and the Florence Bullying and Victimisation Scales. Results: Statistical analysis indicated gender moderated only the interplay between hated self and bullying victimisation. Conclusions: Through a multidimensional approach, these findings provided further insight into the primary factors of self to the phenomenon of bullying victimisation, also yielding further evidence about the key role of gender during a critical developmental stage, such as adolescence. Limitations, implications, and future research directions are discussed.